Academic Youth’s Education and Career Abroad: a Case Study of Sustainable Education in the UK - Račiūnaitė-Paužuolienė, Rasa (Journal of Education Culture and Society, 2021)
Aim. The research aim of this article is to explore academic youth’s education process and career in the UK. The research focuses on Lithuanian students from three prestigious British universities. Methods. The study revealed three questions: the reasons of students choises to study in prestigious higher schools of the UK, students’ satisfaction in terms of their education process; their placement in the labor market, or academic/business career. To answer the research questions qualitative research was conducted by using structured, partly-structured in-depth interviews, the questionnaire forms, discussions, and observation methods. Results. The analysis of the empirical research data revealed that the determining factor of students’ choices was the high quality of the studies and international work perspectives after graduation as well as the rating of the universities and the recommendations of senior fellow students, progressive learning and living environment. Furthermore, they had the possibility to become part of the international social web. The results of the survey indicate that students give more value to individualism emphasizing achievement, critical thinking, high level of education. They also appreciate the possibilities to apply knowledge in real-world setings, also to the career in international business or academic field, which is garanteed by most reputable universities. In such evironment students are encouraged to be responsible actors and to create a more sustainable world (UNESCO (ESD), 2017). Cognitive value. With the help of a case study of education in the UK, the paper reveals the sustainable education perspectives.